Dientamoeba Fragilis in Gaza Strip: a Neglected Protozoan Parasite - Adnan I Al-Hindi (Iranian Journal of Parasitology, 2013)
Background: The aim of this study was to detect Dientamoeba fragilis by iron haematoxylin stain, as well as its prevalence, and association between D. fragilis infection and diarrhoea among patients attending Al-Nuseirate Refugee Camp Clinic, Gaza Strip.Methods: A cross-sectional study was conducted among 319 children and adults with age ranges from (1 to 75) years old, attending Al-Nussirat Clinic, and who were complaining from clinical symptoms, like diarrhoea and abdominal pain.Results: 28 individuals were infected with D. fragilis with a prevalence of 8.8%. The detection of 28 cases infected with D. fragilis was proved using iron haematoxylin stain, but no case was detected by direct smear or formal-ether sedimentation technique. The most frequent symptoms were abdominal pain (96.4%) and diarrhoea (71.4%) in patients with diantamoebiasis and this was statistically significant (P= 0.03). Co-infection between D. fragilis and Entamoeba histolytica/dispar was 50% and between D. fragilis and Giardia lamblia was 7.1%.Conclusion: D. fragilis was present in the patients stool samples and was detected and proved using iron haematoxylin stain.